ANALISIS YURIDIS PELAKSANAAN OLAH TEMPAT KEJADIAN PERKARA (TKP) DALAM PENCARIAN ALAT BUKTI: JURIDIC ANALYSIS OF THE IMPLEMENTATION OF THE EVENTS EVENT (TKP) IN THE SEARCH OF EVIDENCE - Amalia, Reski; Renggong, Ruslan; Shadiq, Amil (Clavia, 2021)
This study aims to identify and explain the function of the crime scene event and the obstacles faced in implementing the crime scene. This study uses empirical research methods. The location of research at the Polrestabes Makassar. Types and sources of data consist of primary data and secondary data. With data collection techniques through interviews, documentation, and observation. The entire legal material is analyzed qualitatively which is presented descriptively. The results of this study indicate that the function of managing the scene of the case is very important because it determines whether the incident that is suspected of being a criminal act is a criminal act or not, clarifies who the perpetrator is, and looks for and collects evidence contained in the processing of the scene of the case for the purpose of investigation. Meanwhile, the obstacles faced by investigators in the execution of the scene of the case are divided into two parts, namely obstacles originating from within the police and obstacles originating from outside the police.